1989
DOI: 10.1152/ajpgi.1989.257.2.g284
|View full text |Cite
|
Sign up to set email alerts
|

Human gastric emptying and colonic filling of solids characterized by a new method

Abstract: Our first aim was to compare 111In-labeled Amberlite IR-12OP resin pellets and 131I-labeled fiber in the assessment of gastric and small bowel transit and colonic filling in healthy humans. Both radiolabels were highly stable for 3 h in an in vitro stomach model and remained predominantly bound to solid phase of stools collected over 5 days [90.5 +/- 2.1 (SE)% for 131I and 87.4 +/- 1.4% for 111In). The lag phase of gastric emptying was shorter for 111In-pellets (30 +/- 11 min compared with 58 +/- 12 min for 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 0 publications
3
145
0
1
Order By: Relevance
“…for 2 days, participants presented to the General Clinical Research Center in the fasted state for gastric emptying and volume measurements using previously validated methods. 13,[17][18][19] After study personnel confirmed that the participant was fasting (8 h) and had taken four doses of the study medication in the prior 2 days, 10 mCi of 99m Tc-pertechnate was injected intravenously. Ten minutes later, a gastric image was obtained with SPECT while the participant was still fasting.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…for 2 days, participants presented to the General Clinical Research Center in the fasted state for gastric emptying and volume measurements using previously validated methods. 13,[17][18][19] After study personnel confirmed that the participant was fasting (8 h) and had taken four doses of the study medication in the prior 2 days, 10 mCi of 99m Tc-pertechnate was injected intravenously. Ten minutes later, a gastric image was obtained with SPECT while the participant was still fasting.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Thus, prior to the study, and based on a two-tailed, unpaired t-test, there was 80% power to detect the following effect sizes in response to treatment: 23% difference in postprandial gastric volume, 54% difference in fasting gastric volume and 48% difference in gastric emptying based on the results in prior studies in healthy human subjects in our laboratory using the same methods. 13,[17][18][19] After the study, we analysed the sample size required to demonstrate a significant effect based on the pooled variance and differences in mean gastric emptying at 4 h and change in gastric volume after the meal.…”
Section: Statistical Analysis and Powermentioning
confidence: 99%
“…12 42 Colonic transit was evaluated by the geometric centre of counts in the colonic regions of interest (ROI). The geometric centre was the weighted average of the proportions of counts in the four ROI of the colon.13 The regions, designated by numbers 1-4 as weighting factors were, respectively, the ascending, transverse, descending, and rectosigmoid colons.…”
Section: Gammacamera Imagingmentioning
confidence: 99%
“…Most prominent are the X-ray (3) and scintigraphic techniques (4), which have been used to monitor orally ingested capsules containing radioopaque material or gamma-emitters. On the other hand, noninvasive techniques such as ultrasound (5), metal detectors (6), magnetic field detectors (7), and dyes (8) have been used to avoid the adverse effects of ionizing radiation.…”
mentioning
confidence: 99%